Three new species of spinicaudatan clam shrimps from Australia, all from gnammas (rock pools) - Timms, Brian V (Zootaxa, 2018)
Recent collections from the remote Kimberley in Western Australia, have added three species to the known fauna of gnammas, Limnadopsis multilineata Timms, 2009 and two new species described herein, Eulimnadia kimberleyensis sp. nov. and Ozestheria pellucida sp. nov.. A further gnamma icon, Paralimnadia laharum sp. nov. is added from the Grampians in western Victoria. The numerous records of clam shrimps from Australian gnammas are examined.